Analisando os analistas: estudo empírico das projeções de lucros e das recomendações dos analistas do mercado de capitais para as empresas brasileiras de capital aberto - Martinez, Antonio Lopo (2004)
The main purpose of this thesis is to analyze the financial analysts of Brazilian firms. By gathering data from the market and analyzing the current performance of the firms, these professionals prepare earnings forecasts and stock recommendations. Using I/B/E/S database, it is presented a broad empirical research of the earnings forecasts and stock recommendations, as well as their information content for the Brazilian capital market. The empirical studies covered the period from January 1995 to June 2003. This thesis starts with the discussion of some concepts and the modus operandi of the financial analysts of Brazilian firms. After a literature review in the area, the empirical studies begin with the analysis of the earnings forecast errors. Some of their characteristics, such as accuracy, bias and precision are investigated in different contexts. After a critical analysis of the informational content for different types of earnings forecast revisions and actual announced earnings deviated form analysts expectations (earnings surprises), evidences of price effects in response to these facts are documented. The last part of this thesis discusses the role of stock recommendations in the Brazilian market. The percentage distribution of stock recommendations is verified as well as the informational content of stock recommendations. Other studies are carried out to verify the performance of the consensus stock recommendations and the effects of downgrades and upgrades of recommendations for Brazilian companies.